Identification and Characterization of Zika Virus NS5 Methyltransferase Inhibitors - Song, Weibao; Zhang, Hongjuan; Zhang, Yu; Chen, Ying; Lin, Yuan; Han, Yanxing; Jiang, Jiandong (Frontiers in Cellular and Infection Microbiology, 2021)
The recurring outbreak of Zika virus (ZIKV) worldwide makes an emergent demand for novel, safe and efficacious anti-ZIKV agents. ZIKV non-structural protein 5 (NS5) methyltransferase (MTase), which is essential for viral replication, is regarded as a potential drug target. In our study, a luminescence-based methyltransferase assay was used to establish the ZIKV NS5 MTase inhibitor screening model. Through screening a natural product library, we found theaflavin, a polyphenol derived from tea, could inhibit ZIKV NS5 MTase activity with a 50% inhibitory concentration (IC50) of 10.10 μM. Molecular docking and site-directed mutagenesis analyses identified D146 as the key amino acid in the interaction between ZIKV NS5 MTase and theaflavin. The SPR assay indicated that theaflavin had a stronger binding activity with ZIKV NS5 wild-type (WT)-MTase than it with D146A-MTase. Moreover, theaflavin exhibited a dose dependent inhibitory effect on ZIKV replication with a 50% effective concentration (EC50) of 8.19 μM. All these results indicate that theaflavin is likely to be a promising lead compound against ZIKV.